Penjadwalan Unit Pembangkit Termal, Sel Surya dan Baterai Menggunakan Metode MIQP - Galih Yudhaprawira; Sarjiya (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2013)
The use of renewable energy to support the power system operation is a way to reduce the energy dependence from fossil resources. Photo voltage (PV) is one of renewable energy suitable used in tropical area because of the availability of adequate sunlight. One of the problems when PVs are interconnected to thermal generation system is how to determine the committed thermal units to serve the load. In this paper, the unit commitment problems of generation system including PVs and battery are solved using Mixed Integer Quadratic Programming (MIQP). Three simulation scenarios are reported which represent the impact of involving PVs and battery in total operation cost. When PVs are involved in the scheduling, they could reduce the power generated by thermal unit as well as total operation cost. Similarly, when battery units are involved, the battery capability to store and release energy also could reduce total operation cost.